2004
DOI: 10.1590/s1413-78522004000400008
|View full text |Cite
|
Sign up to set email alerts
|

Estudo da mortalidade na fratura do fêmur proximal em idosos

Abstract: Foi feito um estudo de revisão sobre a mortalidade na fratura do fêmur proximal em idosos com base nas publicações mais relevantes do período de 1998 a 2002. Foram incluídos 25 artigos relacionados ao assunto, selecionados com base nos bancos de dados Medline e Cochrane, totalizando 24.062 pacientes com mais de 60 anos de idade, que tiveram fratura do fêmur proximal. Quatorze estudos foram prospectivos, oito retrospectivos e três revisões sistemáticas. As taxas médias de mortalidade foram de 5,5% durante a int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
52
5
59

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(119 citation statements)
references
References 22 publications
3
52
5
59
Order By: Relevance
“…(Table 5) When the population was divided by age (60-69, 70-79, ≥ 80 years), there was a progressive increase in the incidence of fractures with increasing age in all groups (male, female, and total population, in Paraná and Brazil), with a predominance in females and in the population of Paraná. (Table 5) the mortality rate was 5.88% during the hospital stay, similar to that observed in a review of 25 studies, 6 which showed an average rate of mortality in the post-fracture period of 11.9%, 19.2%, and 24.9% at 3 months, one year, and two years, respectively. Although the number of fractures was higher in females, mortality rates were greater in males (6.1%), blacks (6.6%), Asians (7.3%), and people 80 years of age or older(8.7%), consistent with national and international literature.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…(Table 5) When the population was divided by age (60-69, 70-79, ≥ 80 years), there was a progressive increase in the incidence of fractures with increasing age in all groups (male, female, and total population, in Paraná and Brazil), with a predominance in females and in the population of Paraná. (Table 5) the mortality rate was 5.88% during the hospital stay, similar to that observed in a review of 25 studies, 6 which showed an average rate of mortality in the post-fracture period of 11.9%, 19.2%, and 24.9% at 3 months, one year, and two years, respectively. Although the number of fractures was higher in females, mortality rates were greater in males (6.1%), blacks (6.6%), Asians (7.3%), and people 80 years of age or older(8.7%), consistent with national and international literature.…”
Section: Resultssupporting
confidence: 85%
“…Advanced age, number of comorbidities, male gender, and presence of cognitive deficits were identified as the main factors related to higher mortality. 6 In addition to high mortality, femoral fracture also presents a high morbidity rate and functional impairment, causing a psychosocial impact with the degree of post-fracture dependence, reaching 30%. 7,8 Total expenditures on hospitalization for femoral fractures in the elderly in Brazil were around 40 million R$ per year in the threeyear period of 2006-2008, representing about 2% of all causes of hospitalization among the elderly.…”
Section: Introductionmentioning
confidence: 99%
“…O maior percentual de óbito e a maior taxa de mortalidade relacionada ao sexo feminino devem ser analisados com cautela, pois aparecem em discordância com outros estudos nacionais 9,26 , nos quais o sexo masculino foi mais susceptível à mortalidade.…”
Section: Resultsunclassified
“…[14,18,22,[24][25][26][27] Proximal femur fracture can be intracapsular (fracture of femoral neck) or extracapsular (transtrochanteric), and must be treated with prosthesis substitution and osteosynthesis with plate and screws, respectively. [28] Intraoperative blood loss can range from 0.5 to 1.5 liters, [29] causing hypovolemia and hypotension. [19,29] Regional anesthesia is more often used in our service in a femur fracture surgery.…”
Section: Introductionmentioning
confidence: 99%
“…[19,29] Regional anesthesia is more often used in our service in a femur fracture surgery. [28] Spinal anesthesia, even under controlled technical principles, can cause hypotension mainly due to sympathic block with a decrease of the systemic vascular resistance and cardiac output. [30] This study aimed to evaluate the postoperative acute renal failure incidence in elderly patients who underwent femur fracture surgery under spinal anesthesia and stratify this failure using RIFLE criteria.…”
Section: Introductionmentioning
confidence: 99%